The silent sea - Cussler, Clive (Cussler, Clive. Oregon files adventures., 2010)
Cabrillo, chasing the remnants of a crashed satellite in the Argentine jungle, stumbles upon a shocking revelation that leads him in search of an ancient Chinese expedition--and a curse that seems to have survived for more than five hundred years.